THE ECONOMIC CONGLOMERATION: A PATH OF DEVELOPMENT OF THE PYME - Herrera García, Beatriz (2009)
This is the first comprehensive study to analyze conglomerates and economic groups in developing countries and transition economies, it provides a comparative framework for the study of contemporary process of privatization, economic and financial liberalization and neoliberal globalization. The main issues that are examined include: the nature of contemporary economic concentration; the new role of the state towards conglomerates and economic groups; and the the effects of economic and political changes on the legitimacy of the state and large companies.